Incidence of heart failure in patients of acute ST elevation myocardial infarction with impaired renal function (Mediscope, 2018)
Ischemic heart disease is a common cardiac disorder and significant cause of mortality and morbidity worldwide. Effective risk stratification is integral to the management of patients with acute coronary syndromes and associated chronic kidney disease may adversely affect acute ST elevation myocardial infarction (STEMI) outcome. This prospective study was conducted in the Department of Cardiology, Chittagong Medical College Hospital after approval of the protocol for the study with duration of one year. For these purpose 100 patients of STEMI diagnosed by clinical, biochemical and ECG criteria were included in the study. After getting serum creatinine level, estimated glomerular filtration rate was calculated and if it is